2021
DOI: 10.1101/2021.01.16.21249861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The management of Moderate Acute Malnutrition (MAM) in children aged 6-59 months: A systematic review and meta-analysis

Abstract: BackgroundMalnutrition is a leading cause of morbidity and mortality in children aged under five years, especially in low- and middle-income countries (LMICs). Although severe acute malnutrition (SAM) is considered the most serious form of malnutrition, moderate acute malnutrition (MAM) affects greater numbers globally and, unlike SAM, guidelines lack a robust evidence-base. This systematic review and meta-analysis assessed the evidence for lipid-based nutrient supplements (LNS), fortified-blended-flours (FBF)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…This suggests that the option of food supplementation is likely to be safe for children across the spectrum of acute malnutrition; however, there is still a need to identify and prioritize those at highest risk ( 11 ). Food supplementation does not necessarily mean RUTF, because studies have seen similar recovery rates when using other lipid-based nutrient supplements; however, meta-analyses have suggested that fortified blended flours are not as effective ( 12 , 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the option of food supplementation is likely to be safe for children across the spectrum of acute malnutrition; however, there is still a need to identify and prioritize those at highest risk ( 11 ). Food supplementation does not necessarily mean RUTF, because studies have seen similar recovery rates when using other lipid-based nutrient supplements; however, meta-analyses have suggested that fortified blended flours are not as effective ( 12 , 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative RUSF formulations that are less expensive and do not include dairy have also been created and evaluated for MAM therapy. To present, there is no consensus on the best effective treatment for MAM and the involvement of component variables like as dairy in the disease 48 .…”
Section: Moderate Acute Malnutrition (Mam) Treatmentmentioning
confidence: 99%